2018
DOI: 10.3390/polym10030236
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Preparation of Amidoxime-Functionalized β-Cyclodextrin-Graft-(Maleic Anhydride-co-Acrylonitrule) Copolymer and Evaluation of the Adsorption and Regeneration Properties of Uranium

Abstract: The β-cyclodextrin-graft-(maleic anhydride-co-acrylonitrule) copolymer (β-CD-g-(MAH-co-AN)) synthesized through radical polymerization reactions of β-cyclodextrin (β-CD) with maleic anhydride (MAH) and acrylonitrule (AN) in the special monomer proportion, chemically modify with amidoxime groups to obtained the new adsorbent, which was terms as amidoxime-functionalized β-cyclodextrin-graft-(maleic anhydride-co-acrylonitrule) copolymer (β-CD-g-(MAH-co-AO)). Based on the characteristic results of Fourier transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…This is accompanied by the incidence of shoulders in the DTG curves ( Figure 4B at temperatures around 270 °C (Tm,3)), which might be related with the chitosan degradation temperature [61]. Further, the functionalized MA-β-CD have the weight loss at 300 °C, consistent with the weight loss of β-CD [62].…”
Section: Thermogravimetric Analysismentioning
confidence: 57%
“…This is accompanied by the incidence of shoulders in the DTG curves ( Figure 4B at temperatures around 270 °C (Tm,3)), which might be related with the chitosan degradation temperature [61]. Further, the functionalized MA-β-CD have the weight loss at 300 °C, consistent with the weight loss of β-CD [62].…”
Section: Thermogravimetric Analysismentioning
confidence: 57%
“…As shown in Figure E, the pore diameters of Fe 3 O 4 @TiO 2 -AO (13 nm) were between those of Fe 3 O 4 (4 nm) and Fe 3 O 4 @TiO 2 (25 nm), which was additional compelling evidence that indicated the formation of an anatase nanosheet layer and amidoxime grafting on Fe 3 O 4 . TGA in Figure F revealed that Fe 3 O 4 @TiO 2 -AO and Fe 3 O 4 @TiO 2 -AO-U­(VI) suffered from appreciable weight loss from 200 to 500 °C compared with Fe 3 O 4 @TiO 2 , and the apparent degradation of Fe 3 O 4 @TiO 2 -AO (∼19% weight loss) indicated that a large number of amidoxime groups had been grafted onto Fe 3 O 4 @TiO 2 . , The hydrophilic ability of the Fe 3 O 4 @TiO 2 -AO composite was evaluated by the dispersibility in aqueous solution. The Fe 3 O 4 @TiO 2 -AO particles remained well dispersed and stable after 10 h, and it took 38 h for the particles to settle down completely (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of N,N′-methylenebisacrylamide enabled the linear molecules to join together, forming a network structure. Then, potassium persulfate (K 2 S 2 O 8 , 0.5 wt %) was added to the mixture and heated to 80 °C in an oil bath for 3 h. The product (denoted as Fe 3 O 4 @TiO 2 -CN) was separated by a magnet and then washed and dried in vacuum at 45 °C for 12 h. 30 The amidoxime-functionalized Fe 3 O 4 @TiO 2 magnetic microspheres were synthesized by treating Fe 3 O 4 @TiO 2 -CN with hydroxylamine solution (NH 2 OH•HCl). Fe 3 O 4 @TiO 2 -CN (0.1 g) was slowly added into a mixture of ethanol and water (volume ratio of 1:1) containing NH 2 OH•HCl with mechanical stirring at room temperature.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…39 Comparing with pristine GO nanosheets, the FTIR spectra of UO x /GO exhibited a span-new peak at 884.81 cm −1 , which could be attributed to the stretching vibration of the O�U�O. 40,41 Meanwhile, the −OH, −COOH, and −C−O peaks all presented significant dampening after the confinement of the oxygen-enriched uranium precursor, further confirming that the uranium precursor was trapped by the oxygen-containing functional groups on the GO nanosheets.…”
Section: Synthesis and Structural Characterizations Of Uomentioning
confidence: 99%